The PGS1 basic helix‐loop‐helix protein regulates Fl3 to impact seed growth and grain yield in cereals. Issue 7 (24th April 2022) - Guo, Xiaojiang; Fu, Yuxin; Lee, Yuh‐Ru Julie; Chern, Mawsheng; Li, Maolian; Cheng, Mengping; Dong, Huixue; Yuan, Zhongwei; Gui, Lixuan; Yin, Junjie; Qing, Hai; Zhang, Chengbi; et al.
Summary: Plant transcription factors (TFs), such as basic helix‐loop‐helix (bHLH) and AT‐rich zinc‐binding proteins (PLATZ), play critical roles in regulating the expression of developmental genes in cereals. We identified the bHLH protein TaPGS1 ( T. aestivum Positive Regulator of Grain Size 1) specifically expressed in the seeds at 5–20 days post‐anthesis in wheat. TaPGS1 was ectopically overexpressed (OE) in wheat and rice, leading to increased grain weight (up to 13.81% in wheat and 18.55% in rice lines) and grain size. Carbohydrate and total protein levels also increased. Scanning electron microscopy results indicated that the starch granules in the endosperm of TaPGS1 OE wheat and rice lines were smaller and tightly embedded in a proteinaceous matrix. Furthermore, TaPGS1 was bound directly to the E‐box motif at the promoter of the PLATZ TF genes TaFl3 and OsFl3 and positively regulated their expression in wheat and rice. In rice, the OsFl3 CRISPR/Cas9 knockout lines showed reduced average thousand‐grain weight, grain width, and grain length in rice. Our results reveal that TaPGS1 functions as a valuable trait‐associated gene for improving cereal grain yield.